CyberStrong : a primer on cyber risk management for business managers - Singh, Ajay; Chowdhry, Ajai(fwd.) (New Delhi Sage, 2021)
"Cyber risk is one of the biggest challenges businesses face in the 21st century. Increasing dependence on technology to run businesses combined with the spate of cyberattacks and reputational risk in recent times has made cybersecurity a top priority for corporates as well as big and small businesses. Limited knowledge of cybersecurity among business leaders and managers is a major barrier for effective cyber-risk management. CyberStrong enables business managers to assess cyber threats, integrate cybersecurity strategy with business goals and build appropriate response systems to deal with cyber risks"--
Includes bibliographical references.
Keywords: Industrial management; Cyberspace; Cyberterrorism